‘Apptivism’: Women’s activism through digital applications to solve invisibilized needs - Yáñez-Valdés, Claudia (2025)
The rise of mobile applications developed by women and for women has significantly expanded, addressing diverse topics such as empowerment, health, and social inclusion. These applications have evolved into a distinct form of digital social entrepreneurship, providing innovative solutions to gender-specific issues. However, there remains limited consensus on whether these initiatives effectively contribute to making women’s needs more visible and addressing gender disparities in digital spaces. This study examines the role of women-oriented applications as a form of digital activism, assessing their capacity to raise awareness, empower users, and drive social change. Using a thematic analysis of 30 mobile applications created by women, we identified key areas where these technologies contribute to gender equity. Our findings demonstrate that women-led applications not only tackle gender-specific challenges but also act as catalysts for digital activism, fostering community-building, empowerment, and the creation of safe digital spaces. Furthermore, these initiatives align with and significantly advance the United Nations Sustainable Development Goals (SDGs), particularly SDG 5 (Gender Equality), SDG 10 (Reduced Inequalities), SDG 3 (Good Health and Well-being), and SDG 12 (Responsible Consumption and Production). Through sentiment and thematic analysis of user feedback, our results indicate that these applications effectively amplify the visibility of women's unmet needs, provide essential resources, and reduce gender gaps in digital participation. Moreover, the study highlights the creation of support networks among users, where women engage in collective problem-solving and shared experiences. The findings underscore the importance of apptivism, the intersection of app development and activism, as a powerful tool to promote gender equity in digital ecosystems. By demonstrating how digital solutions can serve as mechanisms for social change, this study contributes to the understanding of the impact of women-led technological initiatives.